Effect of Direct Fed Microbials (DFM) and Solid State Fermented (SSF) Biomass on Nutrients Digestibility and Rumen Fermentation in Surti Buffaloes - Mathukiya, Gaurang P; Pandya, Paresh R; Rathod, Sunil V; Sarvaiya, Nitesh P; Sorathiya, Kalpesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present study was carried out to evaluate the effect of supplementing Direct Fed Microbials (DFM) and Solid State Fermented (SSF)  biomass for 70 days on body weight, nutrient intake, digestibility and rumen fermentation in adult Surti buffaloes (n=15). The animals  were randomly allotted into three groups, with 5 animals in each group. The animals in the control group (T1) were fed TMR (Roughage  to concentrate ratio of 65:35) without supplement, while the animals in group T2 and T3 were fed TMR with 3% DFM and 3% SSF biomass  on DM basis, respectively. The average initial and final body weight (kg) of animals in T1 (411.8 and 428.8), T2 (412.2 and 433.1), and  T3 groups (415.8 and 438.7, respectively) were more or less similar. None of the probiotics had significant effect on average DMI and  CPI. The average daily DCPI was however significantly (p
Keywords: Buffalo; Direct fed microbials (DFM); Nutrients digestibility; Rumen fermentation; Solid state fermented